Perluasan Tafsiran Asnaf Fakir Dan Miskin Dalam Konteks Pandemik Di Malaysia - Azman Ab Rahman; Nur Wahida Lokman; Muhammad Firdaus Ab Rahman; Md. Yunus Abd Aziz; Hussein 'Azeemi Abdullah Thaidi (Usim Press, 2024)
Volume: 27 No:4 (page: 82-98)